Exposure to Air Pollution from Road Traffic and Incidence of Respiratory Diseases in the City of Meknes, Morocco - Ibrahim El Ghazi; Imane Berni; Aziza Menouni; Mohammed Amane; Marie-Paule Kestemont; Samir El Jaafari (Pollutants, 2022)
For monitoring spatio-temporal variations of nitrogen dioxide (NO2) content, passive diffusive samplers have been deployed in 14 near-road and residential sites for 14 days. In parallel with the winter campaign to measure the NO2 tracer, road traffic counting sessions were carried out on the city’s main roads. The coupling of the results of the measurement campaigns and the counting sessions under Arcgis 9.3 made it possible to determine the areas most affected by automobile pollution and to carry out a high spatial resolution mapping of the pollutant prospected. The results of this study show that atmospheric NO2 concentrations reach maximum values in the city center and decrease towards its periphery. The analysis of the epidemiological situation of the principal diseases related to air pollution in the city of Meknes during the study period (2010–2014) showed that among subjects aged five years and older, acute respiratory diseases occurred more in women than men. The most affected age group was between 15 and 49 years, while asthma attacks were noted mainly among women aged 50 years and older. Acute respiratory illness and asthma attacks were prevalent in the winter and fall. Among children under five years of age, the age group most affected by pneumonia was those under 11 months. Our integrative approach combined spatialized GIS-based health indicators of these diseases, the location of stationary and mobile sources of air pollution, and measured NO2 levels. This combination has made it possible to detect that residents in areas with heavy road traffic are likely to be more affected than those in areas near industrial activity. The habitat type also contributes significantly to the development and exacerbation of the pathologies studied, especially in the districts of the old Medina.